2021
DOI: 10.1136/bmjopen-2020-044456
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with quad bike crashes: a protocol for systematic review of observational studies

Abstract: IntroductionQuad bikes are four-wheeled vehicles, driven off-road on uneven terrains by farmers for work or young adults for leisure. Quad bike accidental crashes result mostly due to the unique ecosystem of uneven terrain, where these unstable vehicles are commonly driven, in addition to numerous distinctive sociodemographic characteristics related to drivers. This is a protocol for a systematic review of observational studies from all geographical regions and demographic groups in the world to summarise the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Agricultural vehicle crashes, loss of control, and lateral rollovers, as well as workers falling or slipping off the tractor are major causes of injury and fatality for farmers ( 35 ). Furthermore, unstable design and limited perceptibility of farm vehicles increase the likelihood of rollover and collision ( 36 ). Agriculture work also involves the use of various types of hazardous equipment.…”
Section: Resultsmentioning
confidence: 99%
“…Agricultural vehicle crashes, loss of control, and lateral rollovers, as well as workers falling or slipping off the tractor are major causes of injury and fatality for farmers ( 35 ). Furthermore, unstable design and limited perceptibility of farm vehicles increase the likelihood of rollover and collision ( 36 ). Agriculture work also involves the use of various types of hazardous equipment.…”
Section: Resultsmentioning
confidence: 99%
“…The study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines for reporting systematic reviews [20] and was prospectively registered online with Prospero [CRD42020170245]. A detailed peer-reviewed study protocol with a preliminary search strategy and inclusion and exclusion criteria has been published elsewhere [28].…”
Section: Methodsmentioning
confidence: 99%
“…The search was initially conducted in June 2020 and was updated twice in March 2021 and on October 6, 2021, to include new publications (LÖ and PM). Five biomedical databases, including PubMed (the US National Library of Medicine), Embase (Elsevier), Scopus (Elsevier), APA PsycINFO (EBSCOhost), and Web of Science (Clarivate), were searched using the search string developed and reported elsewhere [28]. Additionally, the IEEE Xplore Digital Library (Institute of Electrical and Electronic Engineering) and ProQuest Dissertations and Theses (ProQuest) were also searched to cover relevant studies published in engineering and technolog y journals, dissertations, and theses.…”
Section: Information Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…With its desert ecosystem and increasing recreational use, intervention strategies in the Middle East require a closer look at the unique risk factors relating to quad bike crashes. A systematic review of quad bike injuries revealed an alarming absence of research on quad bike crashes in the region [ 3 ]. Out of 196 studies exploring the risk factors of quad bike crashes across the globe, only one study briefly analysed the magnitude and risk factors of quad bike crashes in the Middle East was cited [ 4 ].…”
Section: Introductionmentioning
confidence: 99%